Low prevalence of active COVID-19 in Slovenia: a nationwide population study of a probability-based sample. (November 2020) - Maver Vodičar, P.; Oštrbenk Valenčak, A.; Zupan, B.; Avšič Županc, T.; Kurdija, S.; Korva, M.; Petrovec, M.; Demšar, J.; Knap, N.; Štrumbelj, E.; Vehovar, V.; Poljak, M.
Abstract: Objectives: Accurate population-level assessment of the coronavirus disease 2019 (COVID-19) burden is fundamental for navigating the path forward during the ongoing pandemic, but current knowledge is scant. We conducted the first nationwide population study using a probability-based sample to assess active severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, combined with a longitudinal follow-up of the entire cohort over the next 6 months. Baseline SARS-CoV-2 RNA testing results and the first 3-week follow-up results are presented. Methods: A probability-based sample of the Slovenian population comprising data from 2.1 million people was selected from the Central Population Register ( n  = 3000). SARS-CoV-2 RNA was detected in nasopharyngeal samples using the cobas 6800 SARS-CoV-2 assay. Each participant filled in a detailed baseline questionnaire with basic sociodemographic data and detailed medical history compatible with COVID-19. After 3 weeks, participants were interviewed for the presence of COVID-19–compatible clinical symptoms and signs, including in household members, and offered immediate testing for SARS-CoV-2 RNA if indicated. Results: A total of 1368 individuals (46%) consented to participate and completed the questionnaire. Two of 1366 participants tested positive for SARS-CoV-2 RNA (prevalence 0.15%; posterior mean 0.18%, 95% Bayesian confidence interval 0.03–0.47; 95% highest density region (HDR) 0.01–0.41). No newly diagnosed infections occurred in the cohort during the first 3-week follow-up round. Conclusions: The low prevalence of active COVID-19 infections found in this study accurately predicted the dynamics of the epidemic in Slovenia over the subsequent month. Properly designed and timely executed studies using probability-based samples combined with routine target-testing figures provide reliable data that can be used to make informed decisions on relaxing or strengthening disease mitigation strategies.